HOW DO FOOD INFLUENCERS ON INSTAGRAM AFFECT CONSUMERS’ VISIT INTENTION TO RESTAURANTS IN MACAU? - Ho, Pui I. (University of Saint Joseph, 2023)
This dissertation examines consumers' perceptions of food influencer content on Instagram and the relationship between exposure to food influencer reviews and consumers' intention to visit restaurants in Macau. A mixed-method research design was employed, combining quantitative survey data from 301 responses with qualitative insights from one focus group session involving six participants. The findings suggest that consumers find food influencer content entertaining and inspiring for dining out and exploring new culinary experiences, but they express concerns over its credibility. While food influencer content has a good exposure to consumers, it has a moderate impact on consumers’ restaurant choices, with various factors affecting the relationship. The results highlight the importance of perceived trustworthiness and enjoyability of food influencer content, the visual appeal of food and restaurant environments in photos, and personal relationships in shaping Macau consumers' visit intention to restaurants. The findings can serve as a basis for future research on credibility perceptions of food influencers, the enjoyability of influencer content, and the visual appeal of food and restaurant environments on Instagram. Practically, food influencers should prioritize transparency, authenticity, appealing photos, engaging captions, and leverage the role of personal relationships to increase their impact on consumers' restaurant choices
Keywords: Instagram; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; food influencers; influencer marketing; social media

SINGERS' ONLINE MARKETING STRATEGIES IN GUANGDONG PROVINCE: HOW TO ESTABLISH AND MAINTAIN A STRONG ONLINE PRESENCE FOR EFFECTIVE MUSIC PROMOTION AND FAN ENGAGEMENT - Feng, Qiuyuan (University of Saint Joseph, 2024)
Previous research has explored the development of online music and singers in Guangdong Province; however, there is a gap in understanding how singers establish and maintain a strong online presence through effective online marketing strategies. To fill this gap, this study employs a mixed-methods approach to deeply investigate how Guangdong singers leverage digital platforms for effective music promotion and fan engagement. Online questionnaires were distributed via Xiaohongshu and WeChat, collecting 153 valid responses from fans, which were analyzed to understand interaction methods and their impact on singers. Additionally, semi-structured interviews were conducted with three Guangdong singers and one music company employee, and the interview data were thoroughly analyzed.The findings indicate that Guangdong singers utilize specific social media platforms (such as TikTok) to create and share personalized content and establish direct interactions with fans. These strategies are crucial for successful music promotion and fan engagement. In the highly competitive online music market, adopting such targeted digital marketing strategies allows singers to significantly enhance their visibility and fan engagement. This approach not only holds significant importance for the personal development of singers in Guangdong but also has far-reaching implications for the prosperity of the music industry and the creative economy as a whole
Keywords: Guangdong singer; Internet influence; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; audience engagement; music promotion; online marketing; singer fans

ARTIFICIAL INTELLIGENCE (AI) GENERATED ART & VISUAL COMMUNICATION: ITS EFFECTS ON HUMANS' IMAGINATION, CREATIVITY, COMMUNICATION, AND CULTURE - Cheong, Weng Chim (University of Saint Joseph, 2024)
Technological advancements have enabled machines to offer more efficient assistance to people across several domains. Art and creativity are what distinguish people or societies the most. The arrival of AI has caused a fresh wave of concern among many of us; it is crucial that we evaluate the weight of the positives and the drawbacks of how people employing these technologies will influence societies. Legislation is frequently delayed because of the various revolutions througout history. Along with the difficulties raised in the continuing debate, it is critical to identify a route or alternative to assist existing challenges for artists. This dissertation includes our case studies, analysis, and conclusions, which explain the effects on imagination, creativity, communication, and culture when individuals use AI technologies to create art or/and images. According to our findings, AI technology should be considered as one way to solve problems. The vast majority of created outputs are unable to accomplish the desired reach. Furthermore, even if the ethical issues cannot be resolved, individuals should not ignore it and keep their moral compass. Importantly, we must realise that individuals should always be involved in and influence the intricacies and components of the creative process. However, it is commonly understood that the deployment of artificial intelligence has an influence on people’s communication and societies. There are still no standards, frameworks, or norms on this front of Ai-generated images. This might contribute to an increase in industrial imbalance and discrimination. As a result, to safeguard our individuality, we must take the initiative to uncover any answers or directions that would aid in this scenario. As with any experience, whether internal or external, we should use it to our advantage to apply our creative process, something the computer cannot accomplish. Still, it gives many benefits and is effective in assisting people in completing challenging tasks, so it is smart not to avoid teamwork. Furthermore, because social media and the internet provide powerful expression and communication tools, their advantages should help build universal rules to safeguard artistic work
Keywords: AI-generated art; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; communication; creativity; culture; imagination

THE IMPORTANCE OF VISUAL ELEMENTS IN BRAND COMMUNICATION IN MACAU CASE STUDY: DESIGN OF CULTURAL AND CREATIVE PRODUCTS - Long, On Nei (University of Saint Joseph, 2024)
The research highlights the significance of souvenirs in contributing to the preservation of cultural heritage and communicating cultural messages to tourists. However, a need for more study exists on the visual elements and brand communication employed in designing cultural and creative products that represent local culture. This research aims to investigate the cultural and creative products industry's status and identify the essential visual elements for designing Macau's cultural and creative products. The study also seeks to understand the visual elements and communication strategies that significantly influence product design and brand communication while capturing the image and style of Macau. The research collected 265 valid questionnaires from online participants and interviewed four designers from small local artist brands. The analysis revealed that local consumers prefer products from small local artist brands, but there needs to be a higher brand awareness. Respondents suggested that utilising social media platforms would effectively increase brand awareness and engage with consumers. Furthermore, it was found that Macau's cultural and creative products can integrate various local elements and design styles to represent its unique style. These visual elements are deemed adequate for cultural and creative product design. This research contributes to the creative and tourism industries by providing designers and scholars with insights and references to better comprehend visual and brand communication for local small artist brands
Keywords: Brand Communication; Cultural and Creative Products; Images of Macau; Souvenirs; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Exploring the Impact of the Metaverse on Macau's Fashion Industry Development - Chan, Ka I. (University of Saint Joseph, 2024)
The emergence of the virtual world through social media, technical advancements, digital fashion, and the concept of the Metaverse begs the question of whether Macau's fashion sector can transfer to the virtual sphere. Macau fashion designers have different needs for virtual fashion vs traditional fashion manifestations. The designer's experience, Macau residents' interest in the virtual world and metaverse, and communication inside the metaverse all play an important role in this study. This research study shows our design work, analysis, and conclusions, which explain the concepts and research incorporating the Metaverse virtual platform, virtual characters, user interaction for various target groups, and survey feedback. This detailed research provides a deeper understanding and insights into the Metaverse concept's usefulness in marketing Macau fashion businesses and providing essential information to local Macau fashion designers, fashion industry experts, and Macau people. According to preliminary investigation, utilising avatars and virtual fashion in the virtual world is a novel and promising way for fashion brand operations and expansion. This technique provides cost savings, endless creative options, and effective brand messaging, with the opportunity to predict future virtual fashion trends while keeping a real retail presence
Keywords: Communication; Digital Fashion; Macau's Fashion Industry; Metaverse; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; Virtual World

THE USE OF AI TECHNOLOGY IN MACAO JOURNALISM: A CASE STUDY - Chan, Weng Fai (University of Saint Joseph, 2024)
Artificial Intelligence (AI) is the most advanced technology nowadays and has already been adopted by the media industry globally. Some research has stated that journalists use these technologies to improve their work. Studies found that the extent to which journalists use these technologies depends on the size of their organization and regional circumstances. This study explores how interviewed Macao journalists integrate AI tools into their work, focusing on text processing, translation, and idea generation to improve efficiency and creativity. In addition, respondents expressed that there is not enough information about AI for a small place like Macao. And the problem of application in a “three primary written languages and four spoken languages” environment. At the same time, respondents’ concerns about AI’s accuracy, reliability, and impact on journalistic professionalism are discussed, emphasizing the need for credible and trustworthy AI outputs. This study reveals a significant difference in AI tool adoption between Chinese and Portuguese respondents, with the former group showing a higher inclination towards using these technologies. Therefore, further research is suggested. In the absence of media competition in Macao, the use of AI and its knowledge is spread by journalists sharing it among different organizations, and there seems to be no official decision on the use of AI by media organizations in Macao
Keywords: Artificial Intelligence; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; generative AI; journalism; journalists; media; multicultural; multilingual; newsroom

THE IMPACT OF SOCIAL MEDIA AMONG MACAU BAPTIST COLLEGE SCHOOL STUDENTS: ATTITUDE TOWARDS LEARNING AND RELATIONSHIP WITH PEOPLE - Leong, Fong Hio (University of Saint Joseph, 2024)
This study explores the attitudes of students at Macau Baptist College toward social media usage and its influence on their relationships and academic performance. The research utilized mixed methods to incorporate focus group discussions, in-depth interviews with eight students, eleven teachers, and seven parents, and an online questionnaire administered to 341 students across all college levels. Findings reveal that WeChat is the primary communication tool among college members, significantly facilitating relationships within the school community. Students reported spending extensive time online, especially during holidays, which raises concerns about its impact on academic performance and mental well-being. While many students acknowledge the potential benefits of social media for learning, they also express skepticism regarding the reliability of online information and experience challenges in seeking help due to fears of judgment. The study highlights students' mixed attitudes toward social media, emphasizing the need for digital literacy and guidance to navigate online interactions safely. Ultimately, this research underscores the importance of fostering a supportive environment for students, enabling them to balance their digital engagements with academic responsibilities. Recommendations for parents, educators, and policymakers include: - Promoting responsible social media use. - Enhancing media literacy education. - Facilitating open communication to address online challenges. By addressing these aspects, stakeholders can optimize the positive effects of social media while mitigating its potential drawbacks on students' well-being and academic success
Keywords: Attitude; Learning; Relationship; Social Media; Students; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Effective Promotion for Old Tea Restaurant Base On Marketing Mix Approach After Covid-19 Pandemic In Macau - Ho, Ka Ian (University of Saint Joseph, 2023)
This research paper analyses the marketing efforts and important attributes of Macau tea restaurants that have been open for more than 20 years, especially the digital methods that tea restaurants have used to sustain their business and meet customers' needs in the era of digital transition after the onset of the 2019 Covid 19 pandemic year. Using online marketing channels nowadays become an important tool for communicating with customers today. Despite the old Tea Restaurants in Macau did not put much efforts on digital channels for communication yet, to find out how tea restaurants survive in the rival restaurant industry in Macau, qualitative and quantitative methods were used to see how they meet the needs of their customers. For the quantitative method, an online survey questionnaire in bilingual English and Traditional Chinese was conducted with 280 respondents on customer purchase habits, importance of restaurants’ attributes and social media insights on tea restaurants, and the data was analysis by SPSS for the relationship and significance. For the qualitative method, 7 interviews were conducted with the business owners of the old tea restaurants which that have been opened for more than 20 years, including marketing efforts and their attitudes towards digitalization. To find out the marketing strategy of Macau’s old tea restaurants in the digital transformation era, it was found that “place” and “product” are the most important marketing mix for customers. Tea restaurant owners focus on product quality, and generate “word-of-mouth” which is customer-generated marketing, and is an effective way to influence customers for local tea restaurants. Meanwhile business owners will consider digitalize in the near future as well to match the new young customers’ online habits and the need for “place” such as online delivery platform
Keywords: Macau; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; digitalization; marketing mix; tea restaurant

SOCIAL MEDIA AND UNIVERSITY STUDENTS' PERSPECTIVE OF RELIGION: A COMPARATIVE STUDY OF EVERY NATION IN THE PHILIPPINES AND MACAU - Tabilas, Analeah Marie R. (University of Saint Joseph, 2024)
This research analyzed and compared the Instagram content of Victory Philippines and Every Nation Manila to evaluate its impact on the faith perception of university students associated with these churches. In this digital age, institutions have embraced the shift towards online interactions, including adapting religious practices such as worship services to online platforms. Religious organizations are navigating the dynamics between online and offline communication methods as they adapt to engaging with their audience through social media channels. While previous research has delved into online religious content and virtual church services, no prior studies have specifically compared the social media communication strategies of Every Nation churches in Manila, Philippines, and Macau. The research employed a mixed-method approach, compromising interviews, focus groups, and quantitative content analysis. As per the interviews, these took place with four pastors and four media content creators within the Metro Manila region of Every Nation Philippines, commonly recognized as Victory Philippines, and one pastor and one content creator of Every Nation Macau. These interviews helped gather insights into their thought processes and analyze their social media strategies and plans. Three distinct focus group discussions were carried out, involving 15 undergraduate students from Manila and Macau affiliated with Victory Philippines and Every Nation Macau. The participants were equally divided into three groups. These students also actively engage with the Victory Philippines and Every Nation Macau Instagram posts. These focus group discussions were employed to analyze patterns to understand their thought processes. Furthermore, a quantitative content analysis was carried out on Victory Philippines and Every Nation’s Instagram account as part of the study. Despite the active engagement on social media platforms by Victory Philippines and Every Nation Macau, both organizations maintained a strong offline church community. Interviews conducted indicated that the online activities of these churches significantly influenced the faith of students, while their spiritual growth was further supported by an inclusive offline community. This approach exemplified a multi-generational ethos, fostering collaboration between younger and older members towards the shared objective of evangelism. This research validates the Figuring and Disfiguring theoretical framework of Taylor (2007, apud Åhman and Thorén, 2021). The results of the empirical data may provide strong practical guidance to churches of any size as they build and develop their online presence while strengthening their offline presence
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

COMPARATIVE ANALYSIS IN TELEVISION JOURNALISM “TDM (TELEDIFUSÃO DE MACAU, S.A) AND TVS (TELEVISÃO SANTOMENSE)” NEWSCAST CASE STUDIES - Pinho, Silvino Vaz Sacramento (University of Saint Joseph, 2024)
This study delves into the television news practices of TDM (Teledifusão de Macau, S.A.) and TVS (Televisão Santomense) over the past five years (2018-2023), using a systematic approach, this research begins with an introduction outlining the broadcasters' contexts and influences. A content analysis of a representative sample of news programs from both channels forms the core of the study. To gain deeper insights, the research employs a mixed methodological approach. Qualitative data is gathered through interviews with the chief journalist of TVS and 150 residents from Água Grande and Cauê Districts (Angolares ). Additionally, a quantitative analysis is conducted through an online survey targeting the Community of Portuguese-speaking Countries in Macao, garnering 150 responses. The findings highlight the need for improvements to increase viewership. While both broadcasters cover similar news topics (politics, economics, social issues), their presentation styles differ. TDM and TVS adopt a formal and structured approach, but their visual storytelling techniques reflect cultural and regional preferences. The study then interprets the results, examining historical context, cultural influences, and audience preferences to understand the divergent approaches to television journalism. This comprehensive analysis provides valuable insights to enhance news viewership and offers a deeper understanding of the factors shaping television journalism in these two distinct contexts
Keywords: Macao; Media; Sao Tome and Principe; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; newscasts; television journalism

Teaching Portuguese and Patuá Languages at the University of Saint Joseph and its contribution to the Portuguese and Patuá languages in Macau - U, Elvino Agostinho (University of Saint Joseph, 2024)
This study analyses how to contribute to the Portuguese cultural language in Macau. Macau has a long Portuguese governing history, which has lasted for around 450 years and formed the Portuguese cultural heritage. One of the elements is Portuguese and Patuá languages, the languages the Macau residents used to speak. Since the Portuguese and Patuá cultural heritage influence happened, the Macau government has tried to preserve the Portuguese cultural language as much as possible. In Macau, the University of Saint Joseph is a part of the Portuguese and Patuá language contribution in conducting Portuguese programmes for students. This study aims to find out how to effectively promote the Portuguese and Patuá cultural language via the Macau education system and how to benefit the development of the Portuguese cultural language in Macau. To find out the efficient way of the Portuguese and Patuá cultural language contribution at the University of Saint Joseph, we applied snowball analysis to find the key interviewees to conduct face-to-face semi-structured interviews with six interviewees. The results show that the Portuguese and Patuá cultural languages are vital to the Macau education system, especially for students learning Portuguese. For students, learning Portuguese should be compulsory in Macau
Keywords: Audio-lingual method; Patuá drama; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; cultural difference; cultural identity; learning Portuguese; reading-lingual method; translation theory

GOVERNMENT PUBLIC RELATIONS STRATEGIES IN MACAU: A STUDY ABOUT THE TOURISM PROMOTION - Nip, Si Man (University of Saint Joseph, 2024)
I have met many friendly and patient professors and classmates during my two years of university. I would like to take this opportunity to thank them for the support and encouragement when I encountered difficulties, also professors detailed sharing and explanations in my learning and growing. Taking classes with my job at the same time is a very challenging task, especially in the thesis writing stage, it is difficult to manage the time allocation as well as concentration on thesis writing, and I even had the thoughts of giving up for a few times, but I am very thankful to my supervisor for his continuous support and encouragement during the thesis writing period, and for his attentive guidance whenever I have confusion during the time, he has provided me with a lot of practical and valuable advice, which inspired me a lot. In addition, I would like to thank those who helped me to complete the questionnaire survey. Without their help, I believe it would have been difficult for me to collect enough questionnaires. I would also like to take this opportunity to thank the two interviewees who agreed to be interviewed, as it is a difficult task to conduct interviews as a student in Macau. I would like to thank both for their support of the academic research, and the experience that they shared with us is very important to this study. Last but not least, I would like to thank my family, friends, and colleagues for always providing me with positive support, listening to my concerns, and helping me to overcome difficulties one after another. Once again, I would like to thank all those people who have helped me to complete my thesis
Keywords: Government public relations; Public relation in Macau; Public relation strategies; Public relations; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

COMPARATIVE STUDY ON HOW CORPORATE COMMUNICATION AND MEDIA CHANGE THE WAY ENTERPRISES CONVEY MESSAGES TO AUDIENCES DURING THE PANDEMIC PERIOD AND THE POST-PANDEMIC ERA. CASE STUDY: SJM RESORTS MACAU - Chan, Hoi Man; Simões, José Manuel; Monereo, Zita Carmen (University of Saint Joseph, 2024)
This research study explores the corporate communication strategies and media shifts adopted by large enterprises in Macau during the COVID-19 pandemic and post-pandemic era. Taking SJM Resorts, a large enterprise roots in Macau for over 60 years, as an example to analyze the shift and changes in its corporate communication practices and media usage during the pandemic and post-pandemic era. Moreover, recent literatures on related topic were reviewed to support this research. The researcher invited eight leaders from the case study to conduct semi-structured interviews for qualitative analysis, whilst to distribute 500 e-questionnaire surveys to public for collecting empirical data for quantitative analysis. Issues such as the proportion of offline and online media usage and corporate communication and media strategies and impacts were raised. The study result provides theory and practice reviews for related academic fields. Since there are relatively few research reviews on enterprises’ corporate communication and media landscape during the pandemic and the post-pandemic era at recent stage, this study can fill this gap, provide new research results to the related field as well as enrich the current literature database in related fields
Keywords: Brand marketing; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; corporate communication; digital marketing; offline media; online media